Effects of exposure to a "safe" dose of bisphenol A on male reproductive function and the paternal contribution to the hypothalamic transcriptome profile. (November 2020) - Wu, Nannan; Li, Xianneng; Xu, Fangyi; Tian, Chong; He, Shuiqing; Wang, Yue; Li, Li; Xiong, Qianqian; Zhang, Beibei; Eskedar, Getachew; Ying, Chenjiang
Abstract: The hypothalamus plays key roles in regulating reproduction and energy balance. We determined the transcriptional profile of the hypothalamus (F0 and F1) to identify its relationship with the reproductive function and metabolic phenotypes of rats under BPA exposure and the paternal contribution. Male rats received 35 μg/kg bw/day BPA, 5 μg/kg bw/day ethinylestradiol (EE2) or vehicle via diet. At PND 170, the sexual behaviour of male F0 rats was assessed before mating. The metabolic and reproductive phenotypes and the transcriptional proﬁles of the testis (F0) and hypothalamus were tested in F0 and F1 rats. Male rats exposed to BPA exhibited no changes in fertility, metabolic phenotypes, sperm quality or serum sex hormones, but none of them ejaculated during the test period. Four differentially expressed genes (DEGs) in the F0 hypothalamus and 51 DEGs in the F0 testis were identified in the BPA group. Paternal BPA and EE2 exposure increased the body weight and food intake of male offspring, and 164 and 3433 DEGs were identified in the hypothalamus of BPA- and EE2-treated rats (F1, male), respectively. The highest-ranked function impaired by BPA and EE2 in the F1 hypothalamus was immune function. BPA and EE2 exposure induced alterations in the metabolic phenotype in F1-generation males, and this effect may be related to the altered inflammatory-related signalling pathways in the hypothalamus but neither treatment affected the F0 hypothalamus. Hundreds of genes in the F1 hypothalamus showed changes upon BPA and EE2 treatment. Concern regarding paternal environmental endocrine disruptor exposure should be raised. Graphical abstract: Image 1 Highlights: "Safe" dose BPA affects mating behaviour and transcriptional profile of testis. "Safe" dose BPA do not affect the transcriptional profile of hypothalamus. Paternal "safe" dose BPA increase body weight and food intake of male offspring. Paternal "safe" dose BPA affects transcriptional profile of F1 male hypothalamus. The highest ranked function impaired in F1 hypothalamus was immune function.